IMPLEMENTASI SISTEM DOKER.COM UNTUK BUDIDAYA IKAN KERAPU PADA PT.KINEMA SYSTRANS MULTIMEDIA - Ikhwan Aji Pratama; Yuli Komalasari (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Diseases and pests in grouper fish pose a serious challenge for fish farmers, causing significant losses in production and fish quality. Limited access to up-to-date information and the lack of a centralized platform worsen fish health conditions and impact the sustainability of aquaculture businesses. Therefore, a website-based platform is needed as a digital solution for grouper fish farmers. This research was conducted to develop an information system in the form of the Doker.com website, which provides features to assist farmers in identifying, preventing, and treating diseases and pests in grouper fish. The development method includes the SCRUM methodology for project management and the Design Thinking framework for interface design. This application was implemented using React Vite for interactive frontend development and ExpressJS for backend development. The final result is a Doker.com website platform that provides features such as a digital encyclopedia, prevention and treatment guides, and e-commerce facilities. This platform is expected to increase farmers' knowledge of grouper fish health, improve harvest yields, strengthen the aquaculture community, and support environmental sustainability.